Synthesis and characterization of biocoal from Cymbopogon citrates residue using microwave-induced torrefaction - Tan, I. A. W.; Shafee, N.M.; Mohammad Omar, Abdullah; Lim, L.L.P. (Elsevier B.V., 2017)
This study investigates the effects of microwave-induced torrefaction on the characteristics of lemongrass (Cymbopogon citrates) residue. The effects of microwave power level and reaction time on the proximate and elemental contents, surface morphology, surface chemistry, textural properties, thermal stability, higher heating value (HHV), hydrophobicity, and mass and energy yield of the torrefied lemongrass residue were determined. The development of tubular structure on the torrefied lemongrass residue improved its grindability performance. HHV of 19.37 MJ/kg was achieved by lemongrass residue torrefied at 300 °C. The reduction of H/C and O/C ratios were 14.3% and 60.0%, respectively. Mass and energy yield of the torrefied lemongrass residue was 61.20–81.50% and 66.11–83.85%, respectively. The biocoal showed lower moisture absorbing capacity and was less easily to be segregated into fine particles. The enhancement of physicochemical and thermal characteristics of the lemongrass residue proved the feasibility of converting this biomass into biocoal via microwave-induced torrefaction followed by pelletization.